1978
DOI: 10.1111/j.1365-3040.1978.tb00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brief treatments with benzyladenine on growth and development of watermelon cotyledons

Abstract: Watermelon (Citrullus vulgaris Schrad.) cotyledons were excised from the seed after 24 h of imbibition and incubated for different times (ranging from 1 to 240 min) on filter paper saturated with 0.1 mM BA (benzyladenine) solution. After the incubation in BA the cotyledons were thoroughly rinsed in water and grown for 5 days in darkness on filter paper saturated with distilled water. Continuous presence of BA is not a prerequisite for optimal growth. Several effects of the hormone (stimulation of expansion gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…Earlier work done in our laboratory showed that treatments with lO-' M BA for as short as 1 min are sufficient to evoke longlasting responses in watermelon cotyledons (8). These results suggested that cotyledons are able to take up BA quite efficiently from the external medium.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…Earlier work done in our laboratory showed that treatments with lO-' M BA for as short as 1 min are sufficient to evoke longlasting responses in watermelon cotyledons (8). These results suggested that cotyledons are able to take up BA quite efficiently from the external medium.…”
supporting
confidence: 53%
“…of BA + derivatives) present in the cotyledons and the magnitude of hormonal responses that are observed four days after uptake. This relationship holds regardless of whether a given level of radioactivity has been reached after a short period of uptake or after a long period of uptake followed by washing.Although the action of exogenous cytokinins on excised plant organs is well documented (6,8,9) much less is known about their absorption. Studies on cytokinin uptake have been done with cultured cells (3) and with moss protonemata (5), but comparatively little work has been done with whole organs from higher plants (2, 10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown (6) that continuous exposure to BA is not required for maximal effect. A treatment of 1 to 4 h with 10-' M BA is optimal, whereas a treatment of a few minutes suffices for a significant response.…”
mentioning
confidence: 98%